The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1261/rna.2366310
|View full text |Cite
|
Sign up to set email alerts
|

RPL30 regulation of splicing reveals distinct roles for Cbp80 in U1 and U2 snRNP cotranscriptional recruitment

Abstract: Pre-mRNA splicing is catalyzed by the spliceosome, and its control is essential for correct gene expression. While splicing repressors typically interfere with transcript recognition by spliceosomal components, the yeast protein L30 blocks spliceosomal rearrangements required for the engagement of U2 snRNP (small ribonucleoprotein particle) to its own transcript RPL30. Using a mutation in the RPL30 binding site that disrupts this repression, we have taken a genetic approach to reveal that regulation of splicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Recently, we described how the cap-binding protein Cbc1 is involved in the rapid reprogramming of translation under osmotic stress [33]. Additionally, Cbc1 has been described to be required for the proper splicing of some RP genes [37]. To check whether Hog1 and/or Cbc1 play a role in the drop of RP pre-mRNAs under osmotic stress, we calculated the PMi for several RP genes in mutants hog1 and cbc1 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we described how the cap-binding protein Cbc1 is involved in the rapid reprogramming of translation under osmotic stress [33]. Additionally, Cbc1 has been described to be required for the proper splicing of some RP genes [37]. To check whether Hog1 and/or Cbc1 play a role in the drop of RP pre-mRNAs under osmotic stress, we calculated the PMi for several RP genes in mutants hog1 and cbc1 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Cbp80, the large subunit of the cap-binding complex in yeast (yCBC), was originally identified as Gcr3 in a screen for mutants with reduced glycolytic enzyme expression (Uemura and Jigami, 1992). The yCBC has also been implicated in transcriptional regulation (Hossain et al, 2013; Lahudkar et al, 2011), splicing fidelity, particularly at the 5′SS (Hossain et al, 2009), and the coordination of splicing and transcription (Bragulat et al, 2010; Gornemann et al, 2005). Intriguingly, we have found that CBC expression also changes in response to glucose availability (data not shown), suggesting that the CBC might play a critical role in regulating Gcr1 expression in response to glucose, a model we are currently testing.…”
Section: Discussionmentioning
confidence: 99%
“…The expressed protein contained an amino-terminal HA tag. SpeI and XhoI sites were introduced into the CBP80 pMalE clone ( 33 ) and then CBP80 was cloned into the equivalent sites of the p415-PL plasmid. The PL10 gene in the pRS315 plasmid with a GDH promoter and PGK terminator was as previously described ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sec63 domain of BRR2 was cloned and expressed as previously described ( 42 ). The MalE-Cbp80 protein was expressed and purified as described elsewhere ( 33 ). The amino-terminal GST-tagged eIF4G1 fragments (1-596, 542-952, 882-952) were constructed by cloning the PCR-generated gene fragments into the BamHI-SmaI sites of pGEX-2T (GE Healthcare) and the expressed proteins were purified on glutathione Sepharose columns eluted with 10 mM reduced glutathione, 20 mM Tris–HCl, pH 7.5, 100 mM NaCl and 2 mM dithiothreitol (DTT).…”
Section: Methodsmentioning
confidence: 99%